Household decision-making for the MenACWY vaccination: How parents and adolescents deal with an adolescent vaccination decision. Issue 31 (13th July 2021) - Oostdijk, C.; Van Zoonen, K.; Ruijs, W.L.M.; Mollema, L.
Abstract: Objective: Between 2015 and 2018 The Netherlands experienced increases of invasive meningococcal disease (IMD) serogroup W (MenW), from 0.02 cases/100, 000 people between 2010 and 2014 up to 0.5 cases/100, 000 in 2017. Therefore in 2018 the MenACWY vaccination was introduced in the National Immunisation Programme (NIP) and a catch-up campaign was initiated among adolescents. This study aimed to gain insight into the decision-making process within households regarding the MenACWY vaccination. The focus was on the differences in the decision-making process of parents and adolescents and of those that had accepted the MenACWY vaccination and those that had not, in order to assess how these types of decisions are made within households. Method: We conducted a total of 38 semi-structured interviews in 20 households (7 not vaccinated) with 20 parents and 18 adolescents (18 dyads) across The Netherlands concerning their decision-making process. Interview guides were constructed based on the Precaution Adaption Process (PAP) model. We performed thematic analysis using qualitative data analysis software (MAXQDA). Results: Parents are the main actors in the household decision-making process regarding the MenACWY vaccination. Parents start their decision-making process before adolescents are even aware of the issue. Households in the study took different approaches in involving the adolescent in the decision-making, resulting in three styles of household decision-making: parents decide without the adolescent, parents involve the adolescent, or parents leave it up to the adolescent to decide. Conclusion: Parents influence adolescent reasoning, engagement and involvement during the MenACWY vaccination decision-making. And this is the case both among those that have accepted and rejected the MenACWY vaccination. Adolescent engagement with the MenACWY vaccination decision-making is either short-lived or non-existent. However, the moment offers opportunities to engage adolescents on vaccinations and decision-making, with parents as key figures to promote this.